Depository Receipts in India- Will SEBI Murder It?: Analysis of the SEBI Circulars Dated Oct 10, 2019 and Nov 28, 2019 Regarding Framework for Issue of Depository Receipts - Sandeep Khakase (CV. Proaksara Global Transeduka, 2025)
Depository Receipts (DRs), a structured financial derivative instrument was introduced by the Issue of Foreign Currency Convertible Bonds and Ordinary Shares (Through Depository Receipt Mechanism) Scheme, 1993. Further, the Depository Receipts Scheme, 2014 (2014 DR Scheme) in consonance with the Companies Act, 2013 and other laws started regulating the DRs. After witnessing several manipulative and fraudulent DR Structures in the last decade, the Securities and Exchange Board of India has debarred and penalised several participants and also imposed strict restrictions on DR issuances by rules and Circulars; “Framework for issue of Depository Receipts” on Oct 10, 2019 and Nov 28, 2019 have purported the same. These Circulars have imposed restrictions on eligibility criteria, DR jurisdictions, etc. making the DRs virtually impossible to issue at reasonable cost. This paper aimed at analysing the 2019 Circulars using doctrinal interpretation and literature review to understand if it’s a beginning of the end of DRs from India. The paper found that many restrictions were imposed on the DR issuances whereas “Direct Overseas Listing” may rise up as an alternative instrument for unlisted and mid-cap Indian companies to explore international capital market.